Behind the Privative Space Obstruction. Investigating Visual Perception Privacy, Downtown Algiers’ Mass Housing - Benlakehal, Nadia; Lebdiri, Malika; Djedi, Hadjer (Future Science, 2024)
The present paper brings forth visual perception privacy issue in mass housing in Algiers. Considering a correlation between obstruction rates and visual perception privacy, the case study was selected to measure dwellers’ satisfaction according to Altman’s theoretical framework. A qualitative method was adopted and a semi-guided interview was conducted with 28 downtown mass housing residents in Algiers. On the other hand, to understand outsiders’ perspective regarding downtown dwellings’ perception, the qualitative method was supplemented by a survey involving 94 participants. Both methodological tools were structured according to previous non-participatory observation. Finally, the investigated area appears as being double-scaled: on an urban scale visual perception privacy measurement, people are satisfied, while on the residential scale, dissatisfaction prevails. From outsiders’ perspective, dynamic motions combined to street furniture create a visual protective shield between dwellers and unfamiliar outsiders, as the later perceive environment on a cognitive dimension, while familiar outsiders perceive it on an affective-emotional symbolic dimension.